MENINGKATKAN ASPEK PERKEMBANGAN MOTORIK HALUS ANAKMELALUIKEGIATANMEWARNAIPADAANAK DI PAUD CERIA DI DESA SANTAPAN BARAT - Jumratul Apriani; Nadia Sastia Putri; Karmila Ria Utami (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Each individual early childhood must have their own potential in aspects of their development, especially in aspects of fine motor development. The fine motor skills of children in the Al-Hikmah Kindergarten in Gunung Agung Village are still low. Based on research results, 80% of children whose fine motor skills have not developed properly, that is why the development of fine motor skills in Al-Hikmah Kindergarten is said to be still low. One solution to overcoming fine motor problems is to organize coloring activities. The aim of this research is to stimulate the fine motor development of children in Al-Hikmah Kindergarten through coloring activities so that their fine motor development develops according to their age. This study uses a qualitative research method withdescriptive using research instruments in the form of observation sheets, documentation and interviews.